Dampak Covid-19 Terhadap Pembelajaran Online di Sekolah Menengah Pertama Kota Semarang - Indri Murniawaty; Dwi Puji Astuti; Ahmad Sehabuddin; Devi Cahyaningrum (Proceedings Series on Social Sciences & Humanities, 2021)
Efforts to prevent the spread of the COVID-19 virus implemented in Indonesia in the education sector have resulted in learning at junior high schools in Semarang City using online learning through parental guidance. This study aims to describe the impact of COVID-19 on online learning in Semarang City's first schools. Online learning can use digital technology such as google classrooms, study houses, zoom, video conferencing, telephone or live chat and others. This research is a qualitative research. The informants in this study were students, teachers and parents of junior high school guardians in Semarang City. The results of this study were (1) The impact felt by students on the teaching and learning process at home was that students felt they had more experience than learning in class. (2) From the parent guardian's point of view, the impact felt is the additional cost of purchasing internet quota and parents have to spend time accompanying their children in online learning. (3) The impact felt by the teacher is that not all are proficient in using internet technology or social media as a learning tools.